The Effect of 12 Weeks Aerobic, Resistance, and Combined Exercises on Omentin-1 Levels and Insulin Resistance among Type 2 Diabetic Middle-Aged Women - AminiLari, Zeinab (Diabetes Metab J, 2017)
BACKGROUND: Recent studies have shown that omentin-1 derived from adipokines can affect physiological regulations and some metabolic dis-eases such as type 2 diabetes mellitus (T2DM). METHODS: The purpose of this study was to examine the impact of 12 weeks of aerobic (cycle ergometer), resistance, and combined exercises on omentin-1 level, glucose and insulin resistance indices in overweight middle age women with T2DM. In this study, 60 overweight middle age diabetic women were selected using simple random sampling and they were assigned to three groups of aerobic exercise (n=12), resistant exercise (n=12) and combined exercise (n=13), and one control group (n=15). Exercises were done in a three times per week sessions for a total of 12 weeks. Blood samples were collected before each exercise session and 24 hours after of the last session. RESULTS: Present study showed that fasting blood sugar decreased significantly in all intervention groups, while homeostasis model assessment of insulin resistance (HOMA-IR) decreased only in the aerobic and combined exercises groups. Furthermore, there was a significant increase in the omentin-1 level only in the combined exercise group. CONCLUSION: Compared to aerobic and resistance exercises, 12 weeks of combined exercise was more efficient in improving HOMA-IR and increasing serum omentin-1 among women with T2DM.